OPTIMALISASI LAHAN BUDIDAYA PERTANIAN DENGAN SYSTEM MULTICROPPING SEBAGAI AGROWISATA EDUKATIF DI WONOGIRI - dwi sartono; Dian Purwita Sari (Inisiasi, 2023)
Indonesia is an agricultural country where the agricultural sector plays an important role in supporting national economic growth in the era of globalization, Land is one of the important indicators for the agricultural process, the effectiveness of land in each region is different. This study aims to describe the development of optimization of agricultural cultivation land with the Multiple Cropping system. The purpose of this optimization is the combination of cultivation of food crops and horticultural crops or called integrated agriculture on a certain economic scale, the cultivation process needs to be carried out with the correct technology support pattern and Standard Operating Procedure (SOP). This research uses qualitative research methods. Data collection techniques using interviews, observation and documentation. Data analysis uses qualitative descriptive analysis techniques.  This study was conducted at Barro Tani Manunggal Agritourism. The results of this study show that land optimization techniques with multiple cropping systems are very effective to be applied in various land conditions, and can also be a business field for farmers.